The Susceptibility of 7020 Al-alloys to Pitting Corrosion at Various Heating Temperatures (Journal of the College of Basic Education, 2022)
The present work is aimed to investigate the effect of heat treatments variables ( temperature & time holding) on the tendency of high strength Al-alloys type 7020. The experiments were carried out by heating the specimens at different temperatures (100, 150, 200, 250, 300, 350, 400, 450 and 500 °C) for two periods of holding time, one and two hours.